2017
DOI: 10.1038/s41598-017-05825-9
|View full text |Cite
|
Sign up to set email alerts
|

Global deregulation of ginseng products may be a safety hazard to warfarin takers: solid evidence of ginseng-warfarin interaction

Abstract: Recent global deregulation of ginseng as the table food raises our concern about the possible ginseng-warfarin interaction that could be life-threatening to patients who take warfarin for preventing fatal strokes and thromboembolism while using ginseng products for bioenergy recovery. Here we show that quality-control ginsenosides, extracted from ginseng and containing its major active ingredients, produce dose- and time-dependent antagonism in rats against warfarin’s anti-coagulation assessed by INR and rat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
4
16
0
4
Order By: Relevance
“…A randomized, double-blind, placebo-controlled trial using 20 healthy patients concluded that a 2-week intake of American Ginseng (2 g/d; 1 g twice daily) significantly reduced peak international normalized ratio (INR) and peak plasma warfarin levels (Yuan et al, 2004). In a recent study performed on rats, ginsenosides were reported to significantly enhance the activity of two enzymes known to metabolize warfarin, P450 CYP3A4 and P450 CYP2C9, restoring the levels of coagulation factors II and VII and that of the protein Z, that are usually suppressed by warfarin (Dong et al, 2017). The combined use of Panax ginseng with the monoamine oxidase inhibitor, phenelzine (Nardil), may result in manic-like symptoms (Vogler et al, 1999).…”
Section: Safety Toxicity and Side Effects Of Ginsengmentioning
confidence: 99%
“…A randomized, double-blind, placebo-controlled trial using 20 healthy patients concluded that a 2-week intake of American Ginseng (2 g/d; 1 g twice daily) significantly reduced peak international normalized ratio (INR) and peak plasma warfarin levels (Yuan et al, 2004). In a recent study performed on rats, ginsenosides were reported to significantly enhance the activity of two enzymes known to metabolize warfarin, P450 CYP3A4 and P450 CYP2C9, restoring the levels of coagulation factors II and VII and that of the protein Z, that are usually suppressed by warfarin (Dong et al, 2017). The combined use of Panax ginseng with the monoamine oxidase inhibitor, phenelzine (Nardil), may result in manic-like symptoms (Vogler et al, 1999).…”
Section: Safety Toxicity and Side Effects Of Ginsengmentioning
confidence: 99%
“…It has been suggested that this is due to induction of CYP 3A4 and CYP2C9 enzymes by ginsenosides [21]. St Jone's wort can produce similar effect.…”
Section: Use Of Dietary Supplementsmentioning
confidence: 79%
“…To validate the dual cocktail set, a single oral dose of ketoconazole (10 mg/kg) as a representative Cyp3a inhibitor [ 51 ], a single oral dose of rifampin (20 mg/kg) as a representative Oatp inhibitor [ 21 ], and multiple oral doses of rifampin (20 mg/kg/dy for five days) as a representative Cyp3a and P-gp inducer [ 52 , 53 ] were administered before the dual cocktail substrates. Rifampin and ketoconazole has been widely used to investigate the pharmacokinetic DDIs in human as well as in animals [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the dual cocktail of 10 probe substrates for five CYPs and five transporters was successfully developed without any significant pharmacokinetic DDIs among the probe substrates. This dual cocktail was validated using a representative Cyp3a inhibitor ketoconazole, an Oatp inhibitor rifampin (single administration) [ 21 ], and a repeated rifampin administration, which acts as a Cyp3a and P-gp inducer [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation